Về giải thuật so sánh hai từ trong thuật toán truy nguyên đồng nhất - Nam, Phương Minh; Vương, Lê Tiến (Journal of Computer Science and Cybernetics, 2016)
The problems for automatical indentification algorithm in databases with Latinized names has discussed overview in [2,3], this paper is issuing detail algorithms that compares words of Latinized name followings occurrences probability.